PENYELESAIAN SENGKETA HARTA BERSAMA MELALUI PUTUSAN HAKIM - Rinnanik, Rinnanik (Istinbath : Jurnal Hukum, 2016)
The purpose of marriage is to form households that sakinah, mawaddah, and nurses. One of the consequences of divorce, Division of property is shared. Shared treasures will be disputes when the parties are unable to resolve them peacefully. Hence the need for a third party, in this case is the Court religion. Religious courts is an institution as the implementing authority of Justice for Muslims in Indonesia who have authority in the field of marriage, inheritance, wills, and grants are made on the basis of Islamic law. While the judges are the officials who carry out the powers of the judiciary. In delivering the verdict, there are factors that affect the decision of a Judge of which internal factors and external factors. Internal factors the judge's personal self is concerned about the judge's knowledge, emotions and other external factors are concerned, while speaking in court i.e. sitting things (contains proofs and proof tools) as well as Considerations about the law. Objective verdict based on law and consideration of the matter sitting as well as the Tribunal Judge has knowledge of the matter. The conception of the Division of property jointly applied to the Religious Courts not only refer to existing rules in the compilation of the Islamic law, i.e. half of the parts to each party. But there are also other alternatives in the conception of the Division of property jointly with the Division of the Tribunal judges. Tujuan dari perkawinan adalah membentuk rumah tangga yang sakinah, mawaddah, dan rahmah. Salah satu akibat dari perceraian, adalah pembagian harta bersama. Harta bersama akan menjadi sengketa manakala kedua belah pihak tidak dapat menyelesaikannya secara damai. Oleh karena itu perlu adanya pihak ketiga, dalam hal ini adalah Pengadilan Agama. Peradilan Agama adalah suatu lembaga sebagai pelaksana kekuasaan kehakiman bagi umat islam di Indonesia yang mempunyai wewenang dibidang perkawinan, kewarisan, wasiat, dan hibah yang dilakukan berdasarkan hukum islam. Sedangkan hakim adalah pejabat yang melaksanakan tugas kekuasaan kehakiman. Didalam memberikan Putusan, ada faktor yang mempengaruhi Putusan Hakim diantaranya faktor intern dan faktor ekstern. Faktor intern menyangkut diri pribadi Hakim yaitu mengenai pengetahuan Hakim, emosi dan lain-lain, sedangkan faktor ekstern menyangkut berbicara di Pengadilan yaitu duduk perkara (memuat pembuktian dan alat-alat bukti) serta Pertimbangan tentang hukumnya. Putusan yang obyektif berdasarkan pada duduk perkara dan pertimbangan hukumnya serta Majelis Hakim mempunyai pengetahuan tentang perkara tersebut. Konsepsi pembagian harta bersama yang diterapkan di Pengadilan Agama tidak hanya mengacu kepada aturan yang telah ada di dalam Kompilasi Hukum Islam, yaitu separo bagian untuk masing-masing pihak. Akan tetapi juga ada alternatif lain dalam konsepsi pembagian harta bersama tersebut dengan pembagian dari Majelis Hakim.